Fatigue among children and adolescents with acquired brain injury in a specialized neurorehabilitation setting - Marie-Louise Smidt Proschowsky; Sofie Hur Reimers; Anette Granhøj (Frontiers in Rehabilitation Sciences)
IntroductionWe investigated the fatigue experienced in children and adolescents with acquired brain injury (ABI) undergoing neurorehabilitation.MethodsFatigue was assessed using the pediatric quality of life inventory™ (PedsQL™). Multidimensional Fatigue Scale in 38 participants aged 2–19 years with ABI. Data were collected at enrollment and discharge, either from the participants themselves or their parents. The causes of ABI, including stroke, infection, tumor, and traumatic brain injury), were compared.ResultsParticipant-reported fatigue levels significantly decreased over time (p = 0.005), whereas parent-reported fatigue levels did not show a significant change. Fatigue levels varied by ABI cause, with stroke-associated fatigue having the least impact and infection-related fatigue showing the greatest impact.ConclusionThis study highlights the importance of individualized assessments that consider varying etiological factors and advocates for tailored interventions. Further research is needed to fully understand the long-term impacts of fatigue in this population.